Promotion by Pharmaceutical Industry and Patients’ Perspective in Pakistan - Sadaf Mustafa; Ahmed Osama; Reema Akber; Samana Johari (European Scientific Journal, ESJ, 2018)
The economy of Pakistan is significantly contributed by the pharmaceutical industry which is growing at a rapid rate. For pharmaceutical industry doctor is one of the most important stakeholders because he is the ultimate decision maker rather than the direct user. Pharmaceutical industry focuses on doctors rather than the direct users; BTL i.e. below the line marketing strategy is the basis of marketing in pharmaceutical industry, the importance of sales promotion officers as a marketing technique in pharmaceutical industry cannot be denied and ignored. In order to reach the doctors i.e. the prescribers, pharmaceutical industry takes the help of sales promotion officers that constitutes a major place in pharmaceutical marketing strategies. The connection of pharmaceutical industry with physicians is controversial due to the involvement of personal benefits and clash between money and ethics. Trust is one of the fundamental factors of patient-physician relationships, despite of its recognized significance and efforts to measure patient trust have been quite insufficient. This study investigates the patients’ perspective regarding the sales promotion by pharmaceutical industry, it highlights the viewpoint of one of the most important stakeholders of health care industry i.e. the patients regarding the matter. Questionnaire was used as the research tool to collect the primary data from patients, 100 questionnaires were filled up from a hospital of Karachi.